Pb isotopic domains from the Indian Ocean sector of Antarctica: implications for past Antarctica–India connections - Flowerdew, M.; Tyrrell, S.; Boger, S.; Fitzsimons, Ian; Harley, S.; Mikhalsky, E.; Vaughan, A. (Geological Society Publishing House, 2013)
New feldspar lead isotope compositions of crystalline rocks from the Indian Ocean sector of East Antarctica, in conjunction with the review of data from elsewhere within the continent and from continents formerly adjacent within Gondwana, refine boundaries and evolutionary histories of terranes previously inferred from geological mapping and complementary isotope studies. Coastal Archaean Vestfold and Napier complexes have overlapping compositions and had Pb isotopes homogenized at 2.5 Ga sourced from or within already fractionated protoliths with high and variable U–Pb. Identical compositions from the Dharwar Craton of India support a correlation with these Antarctic terranes. The Proterozoic–Palaeozoic Rayner Complex and Prydz Belt yield more radiogenic compositions and are broadly similar and strongly suggest these units correlate with parts of the Eastern Ghats Belt of India. A strikingly different signature is evident from the inboard Ruker Complex, which yielded unradiogenic compositions. This complex is unlike any unit within India or Australia, suggesting that these rocks represent exposures of an Antarctic (Crohn) Craton. Compositions from the enigmatic Rauer Terrane are consistent with a shared early history with the Ruker Complex but with a different post-Archaean evolution.